Diagnóstico da Produção de Sementes e Mudas no Estado do Amazonas - Marques, Mariana Condé (Instituto Nacional de Pesquisas da Amazônia - INPA, 2020)
The global environmental policy scenario and Brazil’s commitment to restore extensive areas increases the concern about provision of material for implementation of these projects. To understand the situation of the production of seeds and seedlings in Amazonas state, we did a survey of producers in the state with visits to places of production and application of form. The data obtained were analyzed based on descriptive statistics. Seed and seedling production in the state of Amazonas is still incipient compared to provisioning need for restoration commitments in Brazil. To this end, a data base updated and consistent is required, that could stem from Renasem’s record information. The quantity produced is not yet sufficient to re-establish floral richness of the Amazon. A shift to focus on production native species with restoration potential will be needed for this to be the major destinations of planting material. Thus, economic, production-related sector of seed and seedling needs to be extended, however seems to depend on external incentives for operation, specially regarding financial performance.
Keywords: Tecnologia de sementes; Cadeia produtiva da restauração; Produção de sementes e mudas